Lipid-lowering interventions targeting proprotein convertase subtilisin/kexin type 9 (PCSK9): an emerging chapter in lipid-lowering therapy - Constantine E Kosmas; Eddy DeJesus; Rosmery Morcelo; Frank Garcia; Peter D Montan; Eliscer Guzman (BioExcel Publishing Ltd, 2017)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a serine protease that is mainly expressed in the liver but can also be found in the intestine and kidneys. PCSK9 promotes the degradation of low density lipoprotein receptors (LDLR) by reducing their recycling and targeting the receptors for lysosomal destruction, thereby decreasing the rate of removal of LDL-cholesterol from the circulation. Thus, interventions targeting PCSK9 by reducing its expression may lead to significant reductions of LDL-cholesterol and possibly decrease cardiovascular risk. The present review aims to present and discuss the current clinical and scientific data pertaining to lipid-lowering interventions targeting PCSK9.